CONCEPTION RATE DAN SERVICE PER CONCEPTION PADA SAPI PERAH AKSEPTOR INSEMINASI BUATAN DI KUD ARGOPURO KECAMATAN KRUCIL KABUPATEN PROBOLINGGO - Yohana, Nadia; Samik, Abdul; Aksono, Bimo; Sardjito, Trilas; Hermadi, Herry Agoes; Restiadi, Tjuk Imam (Ovozoa: Journal of Animal Reproduction, 2018)
Reproduction is one of essential factor directly affecting profitability in a dairy production system. Some of the reproductive factors that influenced to the developing of dairy cattle of small holder's farmer are Conception Rate (CR) Service per Conception (S/C). The study was conducted to know the CR and S/C of Friesian Holstein in KUD Argopuro, Probolinggo. The data is taken primary and secondary data. Primary data retrieval is done by direct observation, which includes several variables, where the variables include : the identity of the breeder, cages, and feeding and drinking. As for the secondary data obtained by recording the card Artificial Insemination (AI) owned by Inseminator in KUD Argopuro. The data which by collected from this sample are CR and S/C. This research was a case study. The materials used cattle as the acceptors were 10% from 728 lactation cattle. Data from the results of this research on CR (30%) and S/C (2,49). The conclusion of this research for CR the result were lower than normal and S/C the result were higher than normal.